Studies on the text of the New Testament and early Christianity : essays in honour of Michael W. Holmes on the occasion of his 65th birthday - Holmes, Michael W. (Michael William), 1950-; Gurtner, Daniel M.; Hernández, Juan; Foster, Paul; Anderson, Amy S. (Leiden, Netherlands ; Boston, [Massachusetts] : Brill, 2015)
The collection of essays focuses on the twin areas of research undertaken by Prof. Michael W. Holmes. These are the sub-disciplines of textual criticism and the study of the Apostolic Fathers. The first part of the volume on textual criticism focuses on issues of method, the praxis of editing and collating texts, and discussions pertaining to individual variants. The second part of the volume assembles essays on the Apostolic Fathers. There is a particular focus on the person and writings of Polycarp, since this is the area of research where Prof. Holmes has worked most intensively.
Preliminary Material -- Introduction / Daniel M. Gurtner , Juan Hernández Jr. and Paul Foster -- 1 The Late Constantin Tischendorf and Codex Sinaiticus: New Testament Textual Criticism without Them—An Exercise in Erasure History / Eldon Jay Epp -- 2 Patristic Evidence in the Apparatus Criticus of a Greek New Testament / J.K. Elliott -- 3 Nestle-Aland 28 and the Revision of the Apocalypse’s Textual History / Juan Hernández Jr. -- 4 The Edition of the Greek New Testament: A Plea and a Challenge / Jean-François Racine -- 5 Codex 2193 and Family 1 in Mark / Amy Anderson -- 6 Water and Blood and Matthew 27:49: A Johannine Reading in the Matthean Passion Narrative? / Daniel M. Gurtner -- 7 Of Fish and Men: Comparative, Text-Critical and Papyrological Remarks on Matthew 13:47–50 and the Gospel of Thomas 8 / Christina M. Kreinecker -- 8 The Son’s Ignorance in Matthew 24:36: An Exercise in Textual and Redaction Criticism / Daniel B. Wallace -- 9 A Fresh Analysis of P.Oxyrhynchus 1228 (𝔓22) as Artefact / Larry W. Hurtado -- 10 Rightly Dividing the Word: Uncovering an Early Template for Textual Division in John’s Gospel / Charles E. Hill -- 11 Asterius “the Sophist” of Cappadocia: Citations from the Gospel of John as Attested in the Theological Fragments / Roderic L. Mullen -- 12 A Text-Critical Examination of the Johannine Variation / James R. Royse -- 13 The Selection of Greek Manuscripts to be Included in the International Greek New Testament Project’s Edition of John in the Editio Critica Maior / David C. Parker , Klaus Wachtel , Bruce Morrill and Ulrich Schmid -- 14 A Longer Text of Paul: Romans to Galatians in Codex Wernigerodensis (vl 58) / H.A.G. Houghton -- 15 A Short Textual Commentary on Galatians / Tommy Wasserman -- 16 The Text of Galatians 4:25a / Christopher M. Tuckett -- 17 On the Marcionite Prologues to the Letters of Paul / Dirk Jongkind -- 18 Polycarp in the Writings of Ignatius / Paul Foster -- 19 The Devil’s in the Details: The Apocalyptic “Adversary” in the Martyrdom of Polycarp and the Martyrs of Lyons / Paul Anthony Hartog -- 20 The Old Testament in the Apostolic Fathers / James Carleton Paget -- 21 “Witnesses between You and Us”: The Role of the Letter-Carriers in 1 Clement / Peter M. Head -- 22 Defining Exceptions in the Didache / Clayton N. Jefford -- 23 Space, Body, and Church in Ignatius of Antioch: Toward a Spatial Treatment / Harry O. Maier -- 24 Living as a “Christian”: Christian Ethos According to the Writings of Ignatius of Antioch / Tobias Nicklas -- 25 Scripture and Christology in the Preaching of Peter (Kerygma Petri) / Wilhelm Pratscher -- 26 On “Rotten Stones” and a Couple of Other Marginalia in the Shepherd of Hermas / Joseph Verheyden -- 27 Anima naturaliter Christiana – Beobachtungen zum philosophischen und theologischen Hintergrund der Seelenlehre Tertullians / Holger Strutwolf -- Bibliography: Michael W. Holmes -- Bibliography -- Index of Modern Authors -- Index of Subjects -- Index of Citations.
Description based upon print version of record.
English
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Church history -- Primitive and early church, ca. 30-600.; Christian literature, Early -- History and criticism; Bible. -- Criticism, Textual